Probing the foundation of the Mid-Atlantic Ridge - Cannat, M; Karson, J; Hurst, S; Lawrence, R; Jay Miller, D; Agar, S; Barling, J; Casey, J; Ross, K; Ceuleneer, G; Dilek, Y; Fletcher, J; et al. (1995)
ODP Leg 153 drilled five sites on the western wall of the Mid-Atlantic Ridge between 23°20′N and 23°30′N, at distances of 5-35 km south of the Kane Transform (Figure 1). The targets of Leg 153 were extensive exposures of serpentinized peridotites and gabbroic rocks on the western median valley wall. The rock cores collected reveal major compositional and structural variations in both the serpentinites and gabbroic rocks that complement foregoing submersible observations. The samples also provide a sense of the complex igneous, structural, and metamorphic evolution of volumes of these major rock units beyond the scale of hand specimens. -from Author